Remediation and resource utilization of chromium(III)-containing tannery effluent based on chitosan-sodium alginate hydrogel. (15th May 2022) - Guan, Xiaoyu; Zhang, Bingyuan; Li, Dongping; He, Mengyan; Han, Qinxin; Chang, Jinming
Abstract: In this work, chitosan‑sodium alginate polysaccharide hydrogel (CS 0.2 -SA 0.6 (GA 0.3 )) was rationally designed and synthesized via electrostatic and covalent interactions. The structure and morphologies of the hydrogel were characterized, and the results showed CS 0.2 -SA 0.6 (GA 0.3 ) with a layered and loose structure by virtue of glutaraldehyde (GA) cross-linking agent introduction. On the one hand, the porous and loose structure of the adsorbent facilitated the removal of chromium (III) from the tannery effluent. Furthermore, after chromium (III) adsorption, CS 0.2 -SA 0.6 (GA 0.3 )-Cr(III) could be mechanically degraded to CS/SA/GA/Cr(III) sol by a drum, avoiding traditional high-temperature, high-pressure reactor application. Due to the retanning and filling effects of CS/SA/GA/Cr(III) sol, the chemical and physical properties of the finished leather were improved. Based on these, this work aims to provide a strategy that integrates chromium (III)-containing tanning effluent treatment and retanning/filling resource utilization of adsorbent/adsorbate, which is an effective alternative on account of its convenient operation, environmental sustainability, and wide adaptability. Graphical abstract: CS 0.2 -SA 0.6 (GA 0.3 ) was successfully synthesized with a porous and layered three-dimensional structure, realizing the integration of chromium (III) containing tanning effluent treatment and retanning/filling resource utilization of adsorbent/adsorbate. Unlabelled Image Highlights: CS 0.2 -SA 0.6 (GA 0.3 ) hydrogel was rational design via electrostatic and covalent interactions. CS 0.2 -SA 0.6 (GA 0.3 ) dry hydrogel showed a layered and loose structure. The process of Cr(III) adsorption can be predictable by the pseudo-first order and Freundlich model. CS 0.2 -SA 0.6 (GA 0.3 ) displayed high adsorption capacity of Cr(III) from tannery effluent. CS 0.2 -SA 0.6 (GA 0.3 )-Cr(III) were degradable and the degraded sol could be retanning/filling resource utilization.